Prolyl Isomerase Pin1 Directly Regulates Calcium/Calmodulin-Dependent Protein Kinase II Activity in Mouse Brains - Shimizu, Taiki; Kanai, Kenta; Sugawara, Yui; Uchida, Chiyoko; Uchida, Takafumi (Frontiers in Pharmacology, 2018)
Calcium/calmodulin-dependent protein kinase II (CaMKII) is abundant in the brain and functions as a mediator of calcium signaling. We found that the relative activity of CaMKII was significantly lower in the WT mouse brains than in the Pin1-/- mouse brains. Pin1 binds to phosphorylated CaMKII and weakens its activity. For this reason, the phosphorylation level of tau in the presence of Pin1 is lower than that in the absence of Pin1, and microtubule polymerization is not downregulated by CaMKII when Pin1 is present. These results suggest a novel mechanism of action of Pin1 to prevent neurodegeneration.